Child Health Clinical Outcome Review Programme: Health Care Utilisation, Care Pathways and Educational Status in Children and Young People with Adolescent Mental Health problems with a focus on Self harm, Eating Disorders and Anxiety and Depression: IJPDS (2017) Issue 1, Vol 1:111, Proceedings of the IPDLN Conference (August 2016) - Wood, Sophie; John, Ann; Kemp, Alison; Carter, Bethan; Wright, Melissa (International Journal of Population Data Science, 2017)
ABSTRACT Objectives To use routinely collected datasets and data linkage to identify patterns of healthcare utilisation by children and young people (CYP) with adolescent mental health (AMH) disorders across the four UK Nations, with a particular focus on self-harm, anxiety and depression and eating disorders. The analysis will focus on healthcare utilisation during transition from child to adult services and, where possible, on the interface between different care settings e.g. primary and secondary care and health and social care. In addition we will determine the extent to which routinely collected datasets can contribute to an assessment of the health needs and the quality of care that CYP with AMH disorders receive. Approach Data has been requested from the national data providers in each country: The Health and Social Care Information Centre - England The Secure Anonymised Information Linkage (SAIL) databank - Wales Information Services Division – Scotland The Honest Broker Service- Northern Ireland As well as other sources: The Clinical Practice Research Datalink The Paediatric Intensive Care Audit Network. A number of restrictions and information governance regulations have had to be negotiated and put in place in order to access and store the data in the SAIL Databank, Swansea University. Descriptive cross sectional analysis is underway to address the key questions. Rational The project has arisen from the report ‘Overview of Child Deaths in Four UK Countries’ which found that 30-40% of 13-18 year olds were affected by mental health, learning difficulties or behavioural conditions. The diagnosis, management and services available for mental disorders in CYP are of growing concern and a source of controversy in the UK. Transitional care between child and adult services and the interface between primary and secondary/ specialist services, as well as, that between the NHS and other sectors is often disjointed. Thresholds for referral to Child and Adolescent Mental Health Services (CAMHS) are high and many adolescents are treated, at least initially, in primary health care systems. Implications Analysis of routinely collected health datasets has the potential to describe the nature and extent of health needs and health care utilisation for CYP with AMH disorders (self-harm, depression/anxiety, eating disorders). Furthermore the knowledge obtained from using routinely collected healthcare data, will inform future routine data collection across the UK for CYP with AMH disorders.